2019
DOI: 10.1371/journal.pone.0224821
|View full text |Cite
|
Sign up to set email alerts
|

Association between housing tenure and self-rated health in Japan: Findings from a nationwide cross-sectional survey

Abstract: BackgroundMany studies have reported that housing tenure (HT) is associated with health, but little is known about its association in Japan. We investigated the cross-sectional association between HT and self-rated health (SRH) among Japanese adults, taking demographic characteristics and socioeconomic status (SES) into consideration.MethodsWe used data from a nationally representative survey conducted by the Japanese Ministry of Health, Labour and Welfare (28,641 men and 31,143 women aged ≥20 years). HT was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Regarding correlates of SRH by gender and living arrangement groups, findings show similarities and differences in home and community environmental factors associated with SRH. In terms of home environmental factors, living in low-income housing as compared to private housing was a common risk factor of lower SRH across all groups, which is consistent with previous research (Tomioka et al, 2019). Our data suggest that living in low-income housing may be a source of environmental stress associated with low-income or substandard housing conditions that affect the health of older residents.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding correlates of SRH by gender and living arrangement groups, findings show similarities and differences in home and community environmental factors associated with SRH. In terms of home environmental factors, living in low-income housing as compared to private housing was a common risk factor of lower SRH across all groups, which is consistent with previous research (Tomioka et al, 2019). Our data suggest that living in low-income housing may be a source of environmental stress associated with low-income or substandard housing conditions that affect the health of older residents.…”
Section: Discussionsupporting
confidence: 91%
“…Research has largely supported that residents, including older adults, who reported satisfaction with housing quality were more likely to report higher levels of SRH than those who expressed dissatisfaction (Badri et al, 2021;Kno ¨chelmann et al, 2020). Based on the person-in-environment perspective, studies have documented that individuals in low-income housing, including older tenants, are more likely to report lower levels of SRH than those in private housing (Tomioka et al, 2019). Researchers have argued that lowincome housing may be associated with limited physical space, substandard housing conditions, and limited access to recreational facilities.…”
Section: Srh and Home And Community Environmentsmentioning
confidence: 99%
“…Researchers from Korea, Britain, Japan, and New Zealand have all identified a statistically significant relationship between housing tenure and health measures. In contrast with owner-occupiers, renters (either private renters or publicly subsidized renters) were more likely to report poor self-rated health and experience symptoms of depression [ 8 , 13 , 14 , 15 ]. For those tenants aged between 50–85 years, lower levels of quality of life and higher levels of depression symptoms were found to manifest over time [ 8 , 13 , 14 , 15 ].…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…The findings of such research suggest that the built environment influences health through different pathways [ 6 , 7 ]. Specifically, housing conditions such as affordability [ 8 , 9 ], quality [ 10 , 11 , 12 ], and security [ 8 , 13 , 14 ] have been found to impact self-rated health status [ 10 ] and increase the risk of depression [ 15 ] and other diseases [ 9 , 16 ]. In addition, neighborhood characteristics including physical characteristics (e.g., pollution), social–cultural factors (e.g., social cohesion), and community resource access (e.g., recreational facilities) [ 17 , 18 , 19 , 20 ] have each been observed to impact residents’ physical [ 18 , 21 ] and mental health [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…A report showed that private rental houses have poorer quality than public housing and owner-occupied homes in New Zealand, thus having the possibility of different effects on health and well-being 20 , 21 . A cross-sectional study by Tomioka et al 22 on Japanese adults revealed that private renters had poorer self-rated health than other tenure. According to a Japanese White Paper in 2021 of households headed by a married couple with a person aged ≥ 65 years, 87.4% of Japanese older adults were homeowners, 5.5% lived in public rented houses, and 6.9% lived in private rented houses 23 .…”
Section: Introductionmentioning
confidence: 99%